2014
DOI: 10.2106/jbjs.l.01760
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Hill-Sachs Remplissage

Abstract: Postoperative clinical outcome scores were generally good to excellent following arthroscopic remplissage. No studies indicated a significant loss of shoulder motion following the procedure. The failure rate following Hill-Sachs remplissage compared favorably with previously published rates for patients without clinically important Hill-Sachs lesions who underwent arthroscopic Bankart repair alone. The overall complication rate across the studies was low, further supporting the use of this technique along with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
125
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 45 publications
5
125
0
4
Order By: Relevance
“…A case-control study comparing arthroscopic stabilization with stabilization and remplissage (total of 50 patients) showed recurrence rates of 20% and 0%, respectively. 46,58 Summary: The management of engaging HillSachs defects remains contentious. Currently, the Latarjet procedure or remplissage in combination with arthroscopic Bankart repair appear the most acceptable methods in treatment but there have been no randomized controlled trials performed to substantiate their use.…”
mentioning
confidence: 99%
“…A case-control study comparing arthroscopic stabilization with stabilization and remplissage (total of 50 patients) showed recurrence rates of 20% and 0%, respectively. 46,58 Summary: The management of engaging HillSachs defects remains contentious. Currently, the Latarjet procedure or remplissage in combination with arthroscopic Bankart repair appear the most acceptable methods in treatment but there have been no randomized controlled trials performed to substantiate their use.…”
mentioning
confidence: 99%
“…14 These procedures, however, can be technically challenging, often cannot be accomplished arthroscopically, and are associated with potentially serious complications. 3 In the original technique described by Wolf and colleagues, 4 they placed suture anchors into the humeral head through the Hill-Sachs defect and retrieved one limb of the sutures using a sharp penetrating grasper with a 1-cm bridge of infraspinatus tendon. They repeated this process with another anchor before moving to the subacromial space, retrieving the sutures from the subacromial space, and finally, tying the sutures under direct arthroscopic vision.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, complication rates associated with remplissage have been low. 3 The remplissage procedure can be challenging and frustrating for surgeons without prior experience. Problems potentially faced include inadequate visualization, difficulty placing cannulas through the rotator cuff, inaccurate anchor placement, inability to locate the hole through the rotator cuff created by insertion of the awl (if no cannula is used), difficulty retrieving sutures from the subacromial space, inadvertent damage to the sutures while clearing tissue in the subacromial space, and difficulty completing the Bankart repair after the remplissage because of reduced glenohumeral space.…”
Section: 2mentioning
confidence: 99%
“…Their reported loss of motion is greater than many of the other studies that report either no loss of external rotation 15 or less than 2 . 13 Two recent systematic reviews by Buza et al 14 and Leroux et al 16 demonstrated a 2.6 loss in external rotation and no significant loss in external rotation, respectively; the authors concluded clinically that loss of external rotation has not been proven to be an issue after remplissage.…”
Section: Discussionmentioning
confidence: 99%
“…14,16,18,23 The technique we demonstrate is designed to be simple, effective, and reproducible. Through the percutaneous placement of the 2 suture anchors in the single skin and deltoid incision, the double-pulley technique allows reduction of the posterior cuff tissue into the superior posterior humeral defect for a double reinforced fixation.…”
Section: Discussionmentioning
confidence: 99%